The use of the plant “Canarana” (Costus arabicus L.) in the kidney stones treatment in a traditional community in the Northeast of Pará-Amazonia-Brazil (Research, Society and Development, 2020)
The current study aims to register the traditional use of Costus arabicus L., in the treatment of kidney stones in an Amazonian community, and to verify scientific data that collaborate with the use of this medicinal plant. The research approach is qualitative. For that, data collection techniques were used, such as the application of free listing, phytotherapic form, interview, observation, photographs and sample of the species. C. Arabicus is used in the community to treat kidney problems, through tea by decoction. The roots have antiurolytic effects due to a polysaccharide, proven by studies in the field of science, validating the use of the species in renal treatment. In addition, this study considers that there are also active compounds with pharmacological activities present in the stem that help in the treatment of kidney stones, suggesting the need for future studies on their active principles.